Le cinéma de banlieue : un genre instable - Carole Milleliri (Mise au Point)
To name a group of fiction films, showing the social and ethnic specificities of french banlieues, we often use a vague expression: cinéma de banlieue. Which reality can hide the use of this equivocal term ? This paper forsees the study of critical reception as a way to justify the use of this label, to establish a corpus and to define the key lines of a generic « formula ». It intends showing the social value of the development of an unstable film genre, which always depends on the historical context of production of discourses about films - all the more when these put questions on sensitive social issues.